2004
DOI: 10.1046/j.0818-9641.2004.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

The boundaries of the distribution of somatic hypermutation of rearranged immunoglobulin variable genes

Abstract: Summary Available evidence about the mechanisms and distribution of somatic hypermutation (SHM) of rearranged immunoglobulin (IgV) genes is reviewed with particular emphasis on the 5 ′ boundary. In heavy (H) chain genes, the 5 ′ boundary of SHM is the transcription start site; in contrast to κ light (L) chain genes, it is located in the leader (L) intron. DNA-based models of SHM cannot account for this difference. However, an updated reverse transcriptase (RT)-based model invoking error-prone RT activity of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Finally, the RT‐model presents the only scientific explanation available for the 5′ boundary of SHM at Igκ loci. As recently described in detail elsewhere 21 , it is suggested that this boundary in DNA is influenced by processing events within the leader intron at the RNA level. Briefly, binding of small nuclear (sn)RNA and protein factors involved in splicing to sequences within the leader intron of Igκ pre‐mRNA prevents full‐length reverse transcription to the 5′ end of this template and hence locates the common terminus of the cDNA tracts synthesized to the leader intron.…”
Section: Induction Of Phase II Shmmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the RT‐model presents the only scientific explanation available for the 5′ boundary of SHM at Igκ loci. As recently described in detail elsewhere 21 , it is suggested that this boundary in DNA is influenced by processing events within the leader intron at the RNA level. Briefly, binding of small nuclear (sn)RNA and protein factors involved in splicing to sequences within the leader intron of Igκ pre‐mRNA prevents full‐length reverse transcription to the 5′ end of this template and hence locates the common terminus of the cDNA tracts synthesized to the leader intron.…”
Section: Induction Of Phase II Shmmentioning
confidence: 99%
“…As noted by the authors, this model requires the evolution of a defective transcription factor. Recently, one of us (RVB) independently noted that, as UNG2 and pol‐η co‐localize with proliferating cell nuclear antigen (PCNA) in replication foci 96 , 97 and active mismatch recognition by MSH2/MSH6 requires formation of a complex with PCNA 98 , the collision of replication and transcription complexes would thus bring all of the molecules required for phase II SHM potentiation into the vicinity of an Ig locus 21 . PCNA also stimulates the DNA‐dependent 99 and the RNA‐dependent (A. Franklin & R.V.…”
Section: The Collision Modelmentioning
confidence: 99%
See 3 more Smart Citations